Photocatalytic Annulation‐Carbohalogenation of 1, 7‐Enynes for Atom‐Economic Synthesis of Functionalized 3, 4‐Dihydronaphthalen‐1(2H)‐ones. Issue 3 (8th December 2020) - Ji, Wen‐Zhe; Shi, Hao‐Nan; Wei, Ping; Hao, Wen‐Juan; Tu, Shu‐Jiang; Jiang, Bo
Abstract: A general and efficient photocatalytic annulation‐carbohalogenation of 1, 7‐enynes with a wide variety of alkyl halides was reported, which led to the atom‐economic synthesis of functionalized 3, 4‐dihydronaphthalen‐1( 2H )‐ones with good yields and high stereoselectivity under the mild and oxidant‐free conditions. The reaction demonstrated remarkable compatibility regarding alkyl halides as bifunctional reagents, such as ethyl 2‐bromo‐2, 2‐difluoroacetate, ethyl 2, 2‐difluoro‐2‐iodoacetate, perfluorobutyl iodide, bromotrichloromethane, and diethyl 2‐bromomalonate, and enabled wide substrate scope, high functional group tolerance, and 100% atom utilization. Abstract :